Appropriate Tongue Blade Length of the Dingman Mouth Gag for Japanese Pediatric Patients with Cleft Palate and Mandibular Micrognathia. (March 2016) - Satoh, Koji; Aizawa, Takako; Kobayashi, Yoshikazu; Mizutani, Hideki; Yamada, Morimasa
Objective: Our objective is to determine appropriate specifications for smaller tongue blade for Japanese pediatric patients with cleft palate (CP) and mandibular micrognathia. Patients: We investigated 59 patients who underwent palatoplasty. Patients were divided into two groups: the micrognathia (MG) group consisted of 11 patients and the normognathia (NG) group consisted of 48 patients. Interventions: The following five items were investigated retrospectively: (1) gender, (2) cleft type, (3) age at the time of surgery, (4) weight at the time of surgery, and (5) distance from the tongue blade base to the posterior pharyngeal wall (Dis). Result: There was a significant difference (P < .01) in age at the time of surgery and in Dis between groups, but not in weight. The minimum values were 55 mm for the MG group. As for correlations between age and weight at the time of surgery, the P values for the MG and NG groups were .993 and .052, respectively. As for correlations between weight at the time of surgery and Dis, the P values for the MG and NG groups were .987 and .099, respectively. Conclusions: It was difficult to predict Dis on the basis of the patient's age and weight measured preoperatively. The minimum Dis was 55 mm, equal to the length from the base to the tip of the Dingman Mouth Gag tongue blade currently in use, suggesting that a tongue blade of approximately 50 mm in length, shorter than the current minimum specifications, may be appropriate.